2017
DOI: 10.1021/acs.joc.7b01883
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct C(sp2)–H ortho-Arylation of Anilides Using 2-Aminophenylpyrazole as the Directing Group

Abstract: Palladium-catalyzed ortho-arylation of anilides was achieved using 2-aminophenyl-1H-pyrazole (2-APP) as a new directing group. Using Pd(OAc) as the catalyst and AgO as the promoter, mono- and diarylation of anilides were realized in up to 89% isolated yield. Further manipulation of the arylation product may be accomplished by a 2-step sequence involving an acidic hydrolysis of the methylated amide. More interestingly, in the presence of KCO, tandem C-C/C-N cyclization products were obtained for a couple of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In general, low to no yields are usually observed for reactants with highly sterically demanding ortho-substituents, 8,12 but in this case, ortho-substituted aryl iodides reacted smoothly to afford good yields of the target products 4k-m. The directing group might circumvent the formidable steric congestion around palladacyclic intermediates in oxidative addition.…”
Section: Letter Syn Lettmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, low to no yields are usually observed for reactants with highly sterically demanding ortho-substituents, 8,12 but in this case, ortho-substituted aryl iodides reacted smoothly to afford good yields of the target products 4k-m. The directing group might circumvent the formidable steric congestion around palladacyclic intermediates in oxidative addition.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…During our studies, Li's group reported a Pd-catalyzed C(sp 2 )-H ortho-arylation of anilides with APP as a directing group and mixed-valence AgO as a promoter in the preparation of 14 biaryl products [Scheme 1(A)]. 8 Here, we describe a modified pyrazolyl-based-amide bidentate directing group, [4-chloro-2-(1H-pyrazol-1-yl)phenyl]amine (ACPP), that permits a range of Pd-catalyzed ortho-C(sp 2 )-H arylations of aromatic amides [Scheme 1(B)]. In sharp contrast to the case of APP, highly sterically hindered ortho-substituted anilides and aryl iodide partners are tolerated in the reaction, giving good yields, 8 a broader substrate scope, and wider functional-group tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is not only able to promote the reactivity but also to control the regioselectivity for the type of reaction, such as the ortho-, meta-, and para-position of a phenyl ring. 4 The pyridinyl is believed to be the most common directing group due to its good affinity with transition metals, especially for the palladium ion. Therefore, it is often used in our studies with respect to the palladium-catalyzed selective ortho-C−H bond functionalization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Meanwhile, Niu and Song’s group employed Co­(II) and Ni­(II) catalysts and pyridine oxide (PyO) as an auxiliary to realize an sp 2 C–H tandem alkynylation/annulation using silver acetate as an oxidant to gain access to 3-methylene isoindolin-1-one structures [eq 2]. In 2016, we discovered that 2-aminophenyl-1 H -pyrazole (2-APP) as a new removable directing group was efficient for facilitating C–H carbon–nitrogen, carbon–chlorine, and carbon–carbon bond formations. We then proceeded to explore 2-APP’s utility as a directing group for promoting the C­(sp 2 )–H/C­(sp)–H couplings to produce 3-methyleneisoindolin-1-ones [eq 3, PP = 1-phenyl-1 H -pyrazole].…”
mentioning
confidence: 99%